What is the current state of precision rehabilitation? Protocol for a scoping study with a consultation phase - Annie Pouliot-Laforte; Evemie Dubé; Dahlia Kairy; Danielle E Levac (BMJ Open)
Introduction Precision health can be described as the right intervention, at the right time, for the right person, with a focus on monitoring and maintaining health in a longitudinal approach. Despite an increasing focus on precision approaches in medicine, their application in a rehabilitation context remains unexplored. As such, a greater understanding of the current state of the literature is required, in combination with clinician, researcher and healthcare manager perspectives regarding barriers and facilitators to the practical implementation of precision rehabilitation in clinical practice.Objective Describe and map the current state of knowledge regarding precision rehabilitation to identify gaps in knowledge and inform future research directions and clinical implementation strategies.Methods and analysis A scoping study will be conducted following current methodological recommendations (Peters et al, 2021) and reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses—Scoping Review Extension guidelines. A convergent mixed-methods design will combine quantitative and qualitative findings. A search in Medline, CINAHL, Embase, Scopus, Web of Science and PsycINFO databases will be conducted for articles published between 2010 and 2023 referring to the concept of precision rehabilitation. Two reviewers will complete an abstract and full-text review based on eligibility criteria; data will be extracted from accepted papers using a data extraction framework. Results will be aggregated and synthesised using descriptive and thematic analyses. The consultation phase will involve a purposeful sampling of key stakeholders (clinicians, researchers and managers) in large North American rehabilitation centres. Semi-structured individual interviews will be conducted and analysed using deductive thematic analysis. Convergent mixed-methods data analyses will combine quantitative and qualitative datasets to highlight similarities and differences between the current literature on the subject and the understanding of stakeholders.Ethics and dissemination Ethical approval has been obtained from the Research Ethics Board of the Sainte-Justine University Health Centre (no. 2024–6324). Results will be disseminated through professional networks, conference presentations and publications in scientific journals.